NETWORK CENTRALITY, POWER, AND INNOVATION INVOLVEMENT: DETERMINANTS OF TECHNICAL AND ADMINISTRATIVE ROLES. - Ibarra, H. (Academy of Management Journal, 1993)
The reported research investigated the relative impacts of individual attributes, formal position, and network centrality on the exercise of individual power, measured as involvement in technical a...